Active multi-point microrheology of cytoskeletal networks - Paust, Tobias; Neckernuss, Tobias; Mertens, Lina Katinka; Martin, Ines; Beil, Michael; Walther, Paul; Schimmel, Thomas; Marti, Othmar (Beilstein Journal of Nanotechnology, 2016)
Active microrheology is a valuable tool to determine viscoelastic properties of polymer networks. Observing the response of the beads to the excitation of a reference leads to dynamic and morphological information of the material. In this work we present an expansion of the well-known active two-point microrheology. By measuring the response of multiple particles in a viscoelastic medium in response to the excitation of a reference particle, we are able to determine the force propagation in the polymer network. For this purpose a lock-in technique is established that allows for extraction of the periodical motion of embedded beads. To exert a sinusoidal motion onto the reference bead an optical tweezers setup in combination with a microscope is used to investigate the motion of the response beads. From the lock-in data the so called transfer tensor can be calculated, which is a direct measure for the ability of the network to transmit mechanical forces. We also take a closer look at the influence of noise on lock-in measurements and state some simple rules for improving the signal-to-noise ratio.
Keywords: cytoskeleton; intermediate filaments; lock-in technique; microrheology; optical tweezers

(untitled) - Wirtz, D. (Annu. Rev. Biophys., 2009)

(untitled) - Gittes, F.; Schnurr, B.; Olmsted, P. D.; MacKintosh, F. C.; Schmidt, C. F. (Phys. Rev. Lett., 1997)

(untitled) - Mason, T. G.; Weitz, D. A. (Phys. Rev. Lett., 1995)

Theory of simple liquids - Hansen, J.-P.; McDonald, I. R. (Academic Press, 1986)

(untitled) - Mason, T. G. (Rheol. Acta, 2000)

(untitled) - Maier, T.; Boehm, H.; Haraszti, T. (Phys. Rev. E, 2012)

(untitled) - Paust, T.; Paschke, S.; Beil, M.; Marti, O. (Phys. Biol., 2013)

Microscale Diagnostic Techniques - Gardel, M. L.; Valentine, M. D.; Weitz, D. A. (Microrheology, 2005)

Design and applications of Oscillating Optical Tweezers for Direct Measurements of Colloidal Forces - Ou-Yang, H. D. (Wiley, 1999)

(untitled) - Levine, A. J.; Lubensky, T. C. (Phys. Rev. Lett., 2000)

(untitled) - Crocker, J. C.; Hoffman, B. D. (Methods Cell Biol., 2007)

(untitled) - Crocker, J. C.; Valentine, M. T.; Weeks, E. R.; Gisler, T.; Kaplan, P. D.; Yodh, A. G.; Weitz, D. A. (Phys. Rev. Lett., 2000)

(untitled) - Mizuno, D.; Head, D. A.; MacKintosh, F. C.; Schmidt, C. F. (Macromolecules, 2008)

(untitled) - Buchanan, M.; Atakhorrami, M.; Palierne, J. F.; Schmidt, C. F. (Macromolecules, 2005)

Rheology - New Concepts, Applications and Methods - Durairaj, R. (InTech, 2013)

(untitled) - Squires, T. M.; Mason, T. G. (Annu. Rev. Fluid Mech., 2010)

(untitled) - Pelletier, V.; Gal, N.; Fournier, P.; Kilfoil, M. L. (Phys. Rev. Lett., 2009)

(untitled) - Neckernuss, T.; Mertens, L. K.; Martin, I.; Paust, T.; Beil, M.; Marthi, O. (J. Phys. D: Appl. Phys., 2016)

New Methods for Passive and Active Microrheology - Paust, T. (Ulm University, 2013)

(untitled) - Paust, T.; Mertens, K.; Martin, I.; Beil, M.; Marti, O. (arXiv, 2014)

Vorlesungsskript Physikalische Elektronik und Messtechnik - Marti, O.; Plettl, A. (Ulm University, 2013)

(untitled) - El-Ghaoui, L.; Lebret, H. (SIAM J. Matrix Anal. Appl., 1997)

(untitled) - Mandelis, A. (Rev. Sci. Instrum., 1994)

(untitled) - Leitner, A.; Paust, T.; Marti, O.; Walther, P.; Herrmann, H.; Beil, M. (Biophys. J., 2012)

Theory of Elasticity - Landau, L. D.; Lifshitz, E. M. (Pergamon Press, 1986)

(untitled) - Hémonnot, C. Y. J.; Mauermann, M.; Herrmann, H.; Köster, S. (Biomacromolecules, 2015)

(untitled) - Kayser, J.; Grabmayer, H.; Harasim, M.; Herrmann, H.; Bausch, A. R. (Soft Matter, 2012)

(untitled) - Herrmann, H.; Kreplak, L.; Aebi, U. (Methods Cell Biol., 2004)

(untitled) - Herrmann, H.; Aebi, U. (Annu. Rev. Biochem., 2004)

(untitled) - Rogers, S. S.; Waigh, T. A.; Zhao, X.; Lu, J. R. (Phys. Biol., 2007)

(untitled) - Tolić-Nørrelykke, S. F.; Schäffer, E.; Howard, J.; Pavone, F. S.; Jülicher, F.; Flyvbjerg, H. (Rev. Sci. Instrum., 2006)